(untitled) (Engaged Scholar Journal: Community-Engaged Research, Teaching, and Learning, 2017)
Service learning is a form of experiential learning that cultivates academic development, personal growth, and civic engagement. Students contribute to and learn from community. Service learning empowers students, enabling them to recognize their ability to act as agents of social change. Service learning is gaining momentum as a movement, given its ability to prepare students for the “real world” after graduation. The authors of this article come from health sciences, psychology, and environment and sustainability. Here, we illustrate service learning through four case studies: 1) An innovative team-based service-learning course partnering with older adults, healthcare providers and community agencies (Gerontology in Practice, Western University); 2) A unique curriculum design that includes service learning and interdisciplinary graduate problem-based training and research focused on experimental education (Environmental Sustainability, University of Saskatchewan); 3) An international service learning course that combines intensive coursework and a 3-month placement with a non-profit, community-based organization in Africa (Psychology and Developing Societies, University of British Columbia); and 4) An extraordinary example of an institutional-level commitment to service learning involving 50 courses, 40 faculty, 100 community agencies, and 900 students per year (St. Francis Xavier University). Our goal is to inspire other educators to engage in the pursuit of excellence in higher education through service learning.